Production and Marketing Strategies: Reduce Dependence on The Ijon System and Increase Soybean Farmer's Income - Adam, Rosida Panuki; Fattah, Vitayanti; Amirudin, Muhammad; Dwiyanto, Diky; Sastrawan Farid, Erwan (Jurnal Manajemen & Agribisnis, 2023)
The research aims to develop a production and marketing strategy to eliminate dependence on the ijon system and farmers' income. The study was conducted at the Sunda Javanese Transmigration Soybean production center, Dataran Bulan, Ampana Tete District, Tojo Una-Una Regency, Central Sulawesi Province. The sampling technique was the purposive sampling of farmers in Bulan Jaya, Giri Mulyo, Wanasari, Mpoa, and Suka Maju villages. SWOT analysis designs strategic models for increasing production marketing and income. Furthermore, the Revenue and Cost Ratio (R/C) analysis was implemented to see whether the soybean farming business is feasible. The research results show an average production of 2.31 tonnes/Ha/MT and productivity of 1.34 tonnes/Ha/MT. The Production and Marketing Strategy Model as an Effort to Eliminate Dependence on the Ijon System is in Quadrant 1 and Quadrant 2, namely the S-O strategy and S-T strategy. Furthermore, analysis of the R/C ratio (Revenue/Cost) was obtained at = 1.55. The R/C ratio is > 1, so it is concluded that soybean farming is feasible to develop and profitable. Keywords: ijon system, marketing strategy, production strategy, farmers' income, SWOT